Fleksibilitas Pasangan dan Kepuasan Perkawinan - Sekar Ajeng Sawitri; Irwan Nuryana Kurniawan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2009)
The purpose of this reseach was to examine the relationship between couple flexibility and level of marital satisfaction. The respondents were couples with children of their own and they have steady job. Data collected using Couple Flexibility Scale (Olson dan DeFrain, 2003) and Marital Satisfaction Scale. Couple Flexibility has 6 aspect, those were leadership, dicipline, negotiation, role and responsibility, rules and changes whereas Marital Satisfaction has 14 aspects: spouse personality, equality in roles dan tasks, communication, conflict resolution, financial arrangement, spare time activities, sexual relationship, relationship with children, relatives and friends, religious orientation, ambition, love and passion. Data analyzed using Spearman rho technique show that the fleksibility of couple related to their level of marital satisfaction. The contributions (highest to lowest) of each aspect of flexibility to marital satisfaction's level were: disipline (r=0,700), roles and responsibility (r=0,694), leadership (r=0,676), negotiation (r=0,676), changes (r=0,584) and rules (r=0,491). Moreover, the result could also predict the occurance of one aspect in each variable when other aspect in other variable known. Keyword s: couple flexibility, marital satisfacton